Gloss to the judgment of the Provincial Administrative Court in Cracow of 11 January 2021, II SA/Kr 652/20 (approval) - Pelc, Marcin (Studia Iuridica Toruniensia, 2023)
In the commented judgment, the Provincial Administrative Court in Cracow annulled the amendment to the local plan due to the violation of the provisions of the regulation on “Principles of legislative technique”, which identified with a significant violation of the principles of preparing a local plan. The essence of the problem indicated by the Court concerned the difference between the amendment of the local plan and the adoption of a “new” local plan, concerning a situation when the area covered by the planning resolution was already covered by the local plan. The Court’s assessment is welcome above all because of the permanent, lasting in practice since the effective period of the Act of 27 March 2003 on spatial planning and development, interpretation doubts concerning the amendment of local plans. The issue of local plans amendments, raised both in the judicature and in the doctrine, with the position of the voted judgment gains a radical but at the same time optimal solution to this problem. In a way, it forces communal authorities to anticipate planning solutions, and in fact to clearly define the intended planning decisions.